VITAL-Bone Health: rationale and design of two ancillary studies evaluating the effects of vitamin D and/or omega-3 fatty acid supplements on incident fractures and bone health outcomes in the VITamin D and OmegA-3 TriaL (VITAL) - LeBoff, Meryl S. (Contemp Clin Trials, 2015)
RATIONALE: Although vitamin D is widely used to promote skeletal health, definitive data on benefits and risks of supplemental vitamin D alone on bone are lacking. Results from large, randomized controlled trials in the general population are sparse. Data on the effects of supplemental omega-3 fatty acids (FAs) on bone are also limited. DESIGN: The VITamin D and OmegA-3 TriaL (VITAL) is a double-blind, placebo-controlled trial assessing the role of vitamin D3 (2000 IU/d) and omega-3 FA (1 g/d) supplements in reducing risks of cancer and cardiovascular disease among U.S. men aged ≥50 and women aged ≥55. To comprehensively test effects of supplemental vitamin D and/or omega-3 FAs on skeletal health, the VITAL: Effects on Fractures ancillary study is determining the effects of these supplements on incident fractures among 25,875 participants enrolled in the parent trial. Study investigators adjudicate fractures through detailed review of medical records and radiological images (hip and femur). In a complementary ancillary, VITAL: Effects on Structure and Architecture is determining the effects of supplemental vitamin D and/or omega-3 FAs on bone with detailed phenotyping during in-person visits. Comprehensive assessments of bone density, turnover, structure/architecture, body composition, and physical performance are being performed at baseline and 2 years post-randomization. CONCLUSION: Results from these studies will clarify the relationship between supplemental vitamin D and/or omega-3 FAs on bone health outcomes, and inform clinical care and public health guidelines on the use of supplemental vitamin D for the primary prevention of fractures in women and men.